2022
DOI: 10.1155/2022/7947710
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Suprachoroidal and Intravitreal Injection of Triamcinolone Acetonide in Refractory Diabetic Macular Edema due to Epiretinal Membrane

Abstract: Purpose. To compare the efficacy and safety of suprachoroidal and intravitreal injection of triamcinolone acetonide in pseudophakic patients with refractory diabetic macular edema (DME) due to epiretinal membrane (ERM). Study Design. This study is a randomized clinical trial (RCT). Participants. Twenty-three nonvitrectomized pseudophakic eyes of 23 subjects (9 M and 14 F with mean age: 54.8 years) with refractory DME due to ERM. Methods. The eyes were randomized to suprachoroidal triamcinolone acetonide inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…Effects of TA were studied in this research only at 4mg4 mg/0.1 ml of dosage. 21 In contrast to our study, Zakaria et al, divided his patients into three groups. Among these, one group was administered TA (2mg dosage) by intravitreal injection whereas the other two groups received 2mg and 4 mg of drug by suprachoroidal injection.…”
Section: Discussioncontrasting
confidence: 66%
“…Effects of TA were studied in this research only at 4mg4 mg/0.1 ml of dosage. 21 In contrast to our study, Zakaria et al, divided his patients into three groups. Among these, one group was administered TA (2mg dosage) by intravitreal injection whereas the other two groups received 2mg and 4 mg of drug by suprachoroidal injection.…”
Section: Discussioncontrasting
confidence: 66%
“…Localized subconjunctival hemorrhage was noted in one eye (16.6%), no inadvertent intravitreal injection had been occurred, and only one patient (16.6%) reported a localized pain immediately after injection which was controlled by systemic pain killer, our results are consistent with recent publications used the same injection technique. 21,22 Nazari et al reviewed the OCT of 12 eyes (6 patients) with acute VKH and observed that the height of the subretinal fluid in the OCT was correlated with visual acuity, the height of the subretinal fluid in the initial presentation did not correlate with resolution time and final visual acuity. 23 These results are similar to our study, but we find that SCTA helped our patients to gain rapid visual improvement, reduced the dosage of systemic steroids and earlier tapering of steroids as all patients tapered systemic steroids within 3 months from recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Localized subconjunctival hemorrhage was noted in one eye (16.6%), no inadvertent intravitreal injection had been occurred, and only one patient (16.6%) reported a localized pain immediately after injection which was controlled by systemic pain killer, our results are consistent with recent publications used the same injection technique. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…Abdelshafy Tabl et al .’s study was the only study conducted solely in patients with refractory diabetic macular oedema due to epiretinal membrane, and they found a decrease in IOP 1 month after injection. 19 Ateeq et al on the other hand noted a statistically significant rise in IOP at 1 month as well as 3 months post-injection. 20 However, there was consensus regarding there being no statistically significant rise in IOP at 6 months post-injection.…”
Section: Discussionmentioning
confidence: 92%